Antimicrobial Activity of Penicillin G and N-acetylcystein on Planktonic and Sessile Cells of Streptococcus suis - ESPINOSA, IVETTE; BÁEZ, MICHEL; LOBO, EVELYN; MARTÍNEZ, SIOMARA; GOTTSCHALK, MARCELO (Polish journal of microbiology, 2016)
The aim of this study was to investigate the capacity of strains to form biofilms and to evaluate the antimicrobial activity of Penicillin G and N-acetylcystein (NAC) on both sessile and planktonic forms. Only non-typeable isolates of were correlated with a greater biofilm formation capacity. The MCI of Penicillin G and NAC required for inhibiting biofilm growth were higher than the required concentration for inhibiting planktonic growth. The combinations of NAC and Penicillin G showed a strong synergistic activity that inhibited biofilm formation and disrupted the pre-formed biofilm of